Analisis Kebijakan Publik Pengelolaan Resiko Kebanjiran Di Kabupaten Kampar - Nurbit Nurbit; Aldri Frinaldi; Dasman Lanin; Rembrandt Rembrandt (Politeknik Kampar, 2024)
Kampar Regency frequently experiences flooding due to high rainfall and suboptimal spatial planning, significantly impacting the economy and community welfare. Flood risk management requires integrated and evidence-based public policies to enhance mitigation effectiveness. This study employs the Systematic Literature Review (SLR) method to analyze relevant literature, including journal articles, policy documents, and institutional reports. Literature selection was conducted systematically using inclusion and exclusion criteria, and the findings were analyzed thematically.The results indicate that flood risk management in Kampar faces challenges such as a lack of inter-agency integration, limited resources, and low community participation. Technology-based policies, such as early warning systems, are deemed promising but have not been fully implemented.